Given the system of equations:
![\begin{gathered} 2x+2y=6 \\ 2x-2y=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/gq4t4jg1d1lzlsxyqvc0chwiasbbnpd0yn.png)
we can solve it using elimination by directly adding both equations to get the following:
![\begin{gathered} 2x+2y=6 \\ 2x-2y=6 \\ ---------- \\ 4x=12 \\ \Rightarrow x=(12)/(4)=3 \\ x=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/rdbug2r40ym9xq88nexraeeibekakyp57x.png)
now that we have that x=3, we can find y using this value on any of the two equations:
![\begin{gathered} 2x+2y=6 \\ x=3 \\ \Rightarrow2(3)+2y=6 \\ \Rightarrow6+2y=6 \\ \Rightarrow2y=6-6=0 \\ \Rightarrow2y=0 \\ y=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/mt0vsj7f7hhfhfbhudx3ywbkd83bozraco.png)
therefore, the solution of the system is (3,0)